Graphene-based THz antenna with a wide bandwidth for future 6G short-range communication - Md. Kawsar Ahmed; Md. Sharif Ahammed; Md. Ashraful Haque; Narinderjit Singh Sawaran Singh; Jamal Hossain Nirob; Redwan A. Ananta; Kamal Hossain Nahin; Liton Chandra Paul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
In this study, we present the design and investigation of a terahertz (THz) frequency antenna optimized for the 2-10 THz range, featuring both single-element and multiple-input multiple-output (MIMO) configurations, with a focus on industrial and innovative applications to enhance future 6G communication systems. The antenna, constructed on a polyimide substrate with dimensions of 90×30 µm, achieves a bandwidth from 4.0328 to 10 THz. The MIMO configuration, which includes two ports, demonstrates excellent isolation with a value of -27 dB. The proposed antenna system achieves a gain of 12.38 dB and an efficiency of 89%, making it highly appropriate for THz communication applications. Furthermore, the envelope correlation coefficient (ECC) of 0.002 and diversity gain (DG) of 9.99 affirm the antenna’s effectiveness in MIMO systems. A resistance inductance capacitance (RLC) circuit model was employed to accurately represent the S11 curve, ensuring precise characterization of the antenna’s performance. These results underscore the probability of the proposed antenna for high-speed, short-range communication systems.